Die Anwendung der Theorie von Molina und Albir beim Übersetzen der Songlyrik Die Reise von Max Giesinger - Budiono, Tasya Negara Hapsari; Rosyidah, Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
Music, particularly in its form of songs, has played an important role in humanities for centuries. Aside from being an entertainment medium, songs contain lyrics that also represent a literary work named poetry. Both lyrical and musical essences in songs are often used to express one’s feelings. Therefore, the translation process of the lyrics of a song is highly necessary for the song to be widely enjoyed. Based on the background, this research aims to implement there translation techniques of Molina & Albir namely modulation, established equivalence, and amplification in a song titled Die Reise by Max Giesinger, and describe the translated lyrics by each technique. This research employs descriptive qualitative method with read, act, and note technique and the analysis data tables as a supporting instrument. The findings reveal that the song Die Reise by Max Giesinger has 13 lines to be translated by established equivalence, 8 lines by modulation, and 3 lines by amplification. Out of 36 lines in total, the researcher manages to translate 24 lines using three of Molina & Albir’s translation technique.Keywords: translation technique, song lyric, Molina and Albir